Методы модернизации первичной переработки нефти - Правдина, А. Ю.; Бубликова, Е. В.; Манойло, Ю. А.; Моисеев, Виктор Федорович (НТУ "ХПИ", 2010)
У статті розглянутий технологічний процес первинної переробки нафти, що поступає з свердловини на родовищі, з подальшим відділенням води. Запропоновані методи глибшого очищення стічних вод, що утворюються, які призначені для подачі в пласт.

The technological process of the primary processing of oil, acting from a mining hole on a deposit is considered in the article, with the subsequent separation of water. The methods of more deep cleaning of appearing waters of sewers, which are intended for a serve in a layer, are offered.
Keywords: нефтепереработка; экологические проблемы; пластовые воды; очистка сточных вод; отстойный аппарат